Prevalence and correlates of alcohol dependence disorder among TB and HIV infected patients in Zambia. - Rebecca O'Connell; Nathaniel Chishinga; Eugene Kinyanda; Vikram Patel; Helen Ayles; Helen A Weiss; Soraya Seedat (PLoS ONE)
Objectives To determine the prevalence and correlates of alcohol dependence disorders in persons receiving treatment for HIV and Tuberculosis (TB) at 16 Primary Health Care centres (PHC) across Zambia. Methods 649 adult patients receiving treatment for HIV and/or TB at PHCs in Zambia (363 males, 286 females) were recruited between 1st December 2009 and 31st January 2010. Data on socio-demographic variables, clinical disease features (TB and HIV), and psychopathological status were collected. The Mini International Neuropsychiatric Interview (MINI) was used to diagnose alcohol dependence disorder. Correlates of alcohol dependence were analyzed for men only, due to low prevalence in women. Univariable and multivariable logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI), using general estimating equations to allow for within-PHC clustering. Results The prevalence of alcohol dependence was 27.2% (95%CI: 17.7-39.5%) for men and 3.9% (95%CI: 1.4-0.1%) for women. Factors associated with alcohol dependence disorder in men included being single, divorced or widowed compared with married (adjusted OR = 1.47, 95%CI: 1.00-2.14) and being unemployed (adjusted OR=1.30, 95%CI: 1.01-1.67). The highest prevalence of alcohol dependence was among HIV-test unknown TB patients (34.7%), and lowest was among HIV positive patients on treatment but without TB (14.1%), although the difference was not statistically significant (p=0.38). Conclusions Male TB/HIV patients in this population have high prevalence of alcohol dependence disorder, and prevalence differs by HIV/TB status. Further work is needed to explore interventions to reduce harmful drinking in this population.